Effect Of Subacute Dose Of Mitragyna Speciosa Korth Crude Extract In Female Sprague Dawley Rats - Rani Sakaran; Faizah Othman; Zar Chi Then; Srijit Das (Engineering and Technology Publishing, 2024)
Mitragyna speciosa Korth (MS) leaves are widely used as a traditional remedy. The main aim of the present study was to observe the subacute toxicity of MS crude extract on the liver, kidney and uterus in female Sprague Dawley rats. Thirty two rats (150-200g) were randomly divided into four groups: control acute (CA); control subacute (CS); experimental acute (EA) and experimental subacute (ES). CA and CS groups were only given 15% Tween-80. Group EA rats were administered single oral dose of 1000mg/kg MS extract for 14 days. Group ES rats were administered repeated dose of 500 mg/kg MS methanol for 28 days. Liver of ES group showed severe sinusoidal congestion with enlarged hepatocytes and numerous vacuolation compared to EA group. The lining of epithelial cells of uterine tissue in ES group showed more vacuolated cells with increasing in height. No changes were observed in kidney with both doses.